From Rome to Beijing: symposia on Robert Jewett's Commentary on Romans - Yeo, Khiok-Khng (Kairos Studies, 2013)
"A round-table discussion in which scholars from all over the world offered their assessments of Robert Jewett's ground-breaking Romans Commentary"--Publisher's description
Includes bibliographical references and index
Keywords: Jewett, Robert; Bible